Microbiological, biochemical and biogenic amine profiles of Terrincho cheese manufactured in several dairy farms - Ana I E Pintado (2008)
Terrincho is a Portuguese traditional cheese, bearing a protected denomination of origin (PDO) status, which is manufactured from raw ewes' milk and ripened for a minimum period of 30 d. The objectives of this research effort were to characterize the microbiological and biochemical profiles of this cheese, manufactured in several dairy farms during the winter cheesemaking season (December through March), and establish tentative correlations between these profiles and formation of biogenic amines. For this goal, 29 cheeses from five batches, manufactured in as many dairy farms located throughout the PDO region, were analysed. The viable numbers of the total (mesophilic) microflora, enterococci, lactococci, lactobacilli, enterobacteria, staphylococci, pseudomonads, yeasts and moulds were determined by 30 d, following classical plate counting on specific media. Free amino acid and biogenic amine contents were determined by reverse-phase high-pressure liquid chromatography. The concentration of biogenic amines correlated well with microbial viable numbers, in both qualitative and quantitative terms; significant correlations were observed between enterococci and phenylethylamine (r = 0.868, p < 0.0001), and between lactococci and cadaverine (r = 0.646, p = 0.002) and tyramine (r = 0.868, p < 0.0001). On the other hand, 220 g of Terrincho cheese would have to be consumed at a given time if the threshold of worst case risk was to be attained, which appears unrealistic for a typically single-doses meal ingredient. This study has contributed to deepen the knowledge on the microbiological and biochemical features of a unique Portuguese cheese throughout ripening, and to rationalize its safe consumption in terms of biogenic amines.